A comparative study of the effects of high temperature stress on the reproductive growth in two main strawberry cultivars - Ledesma, Nadine Adellia A. (Animo Repository, 2004)
The strawberry is one of the most popular fruits in the northern hemisphere where most of its production areas are also located. The optimum temperature range for strawberry growth and fruit production is between 10-26°C, thus areas with mild summer and winter temperatures are suitable for its cultivation. This is why strawberry production is concentrated along the temperate zone and also why production is normally high during the winter and spring seasons and practically absent during the summer and early autumn seasons. There is strawberry production in sub-tropical and tropical climates, although on a much smaller scale than in the temperate zones. Because strawberry plants need low temperatures to induce flowering, production in warmer climates is possible only at higher elevations where the night temperatures can fall below 15°C in winter. Due to this limited temperature range for growth, the plant is highly sensitive to changes in air temperature. Furthermore, it is well known that the reproductive stage is the most sensitive to high temperatures in many crops. It is, therefore, necessary to gather more knowledge on the effect of high temperatures on the reproductive growth of the strawberry. However, genetic and physiological studies on the resistance or tolerance to abiotic stresses such as drought, salt stress, winter and spring frost, and heat stress, have only recently been gaining attention. Therefore, in this study we examined both the physiological and molecular responses of strawberry plants to high temperature stress during its reproductive stage by comparing the performance of two main cultivars in Japan. The physiological responses to high temperatures were determined in terms of pollen quality and performance as well as fruit set and fruit growth. For a better understanding of the overall system involved in the high temperature stress response, protein expression patterns in the two strawberry cultivars were also investigated.